ASPECT IN GERMAN AND SERBIAN LANGUAGE FROM THE PERSPECTIVE OF COGNITIVE LINGUISTICS (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
The aim of this paper is to analyse the category of aspect by using the findings and conclusions made by cognitive linguistics, and primarily construction grammar as defined by Goldberg. Dynamic constructions grammar proposes that a construction plays the key role in language, being a stored pairing of form and function. This allowed a deviation from the usual perception of the category of aspect, or from the long-established analysis of verbs exclusively. This allowed the category of aspect to be examined in a different way. In this paper we managed to study all the elements of language that can be the carriers of aspectual meaning, in both German and Serbian laguage, which include verbs a prototypical element, but also verb phrases and multiple nominal or adverbial lexemes and the context.
Keywords: aspect, construction, cognitive linguistics, specific verbal aspect of Serbian language “glagolski vid”, contrastive linguistics